PhysioCAFUN: a competency-based curriculum development guideline to strengthen physiology education in Africa - (:unkn) unknown (My University, 2025)
We described the development of Physiology Curriculum for African Universities (PhysioCAFUN), a competency-based curriculum development guideline to promote physiology education in Africa. This freely accessible resource document should help African universities where there is a dearth of physiologists and thus aid in drafting a curriculum suitable for their local needs. Likewise, it should assist universities globally where physiology programs are already in place to benchmark and/or revise their curriculum as may be needed.
Keywords: African Research